SOIL CARBON STORAGE AND NITROGEN AND PHOSPHOROUS AVAILABILITY IN LOBLOLLY PINE PLANTATIONS OVER 4 TO 16 YEARS OF HERBICIDE AND FERTILIZER TREATMENTS - Sartori F.; Markewitz D.; Borders B.E. (My University, 2007)
The impact of extended herbicide (H) and annual fertilizer (F) treatments on the mineral soil carbon (C) pool and nitrogen (N) and phosphorous (P) availability were analyzed in managed loblolly pine (Pinus taeda L.) plantations in the Piedmont of Georgia in stands ranging from 4 to 16 years old. Mineral soil C, N, P, and extractable P were measured in 66 plots in three locations comparing H, F, and their combination HF to the Control plots. Soils were sampled in January 2000 near Eatonton (n = 40), in August 2001 near Athens (n = 12), and in March 2003 near Dawsonville (n = 14). In addition, twelve plots (two H and two HF at each location) were measured on 17 dates using a mixed bead resin core technique to estimate mineral soil N availability. At all three study locations the H treatment tended to deplete the mineral soil C pool while, overall, the F treatments did not determine any significant mineral soil C increase. The soil C pool (0- to 50-cm depth) was depleted by about 5 Mg C ha−1 under the H-treated plots near Eatonton. The HF plots had much higher resin-extractable N than the corresponding H plots in all months of the year. At a plot level, HF values ranged from about 9 to 3,195 μg N g−1 resin while H values ranged from about 4 to 858 μg N g−1 resin. The corresponding annual cumulative resin-extractable N ranged from about 13 kg N ha−1 in the H to about 372 kg N ha−1 in the HF. Extractable P values were also elevated in all F-treated plots. Fertilization and herbicide treatments favored C sequestration only in the aboveground biomass. No significant change was observed in the mineral soil C pool, despite the generally observed increases in soil available N and P.
Keywords: SOIL CARBON SEQUESTRATION; FERTILIZATION; HERBICIDE CONTROL; SOIL AVAILABLE NITROGEN; SOIL EXTRACTABLE PHOSPHOROUS